Regenerative grazing and grassland management enhance soil extracellular enzyme activity and alter microbial nutrient acquisition - Kaitlin J. Watson; Charlotte J. Alster; Jim L. Moir; Leo M. Condron; Alistair D. Black (Agriculture, Ecosystems & Environment, 2026)

Effect of phosphogypsum application on aluminum speciation in acid pasture soils - Moussa Bouray; James L. Moir; Leo M. Condron; Niklas J. Lehto; Mohamed Bayad; Mohamed El Gharous; Khalil El Mejahed (Journal of Soils and Sediments, 2022)

Potential phosphorus losses from grassland soils irrigated with dairy factory wastewater - C. A. Lizarralde; R. W. McDowell; L. M. Condron; J. N. Brown (Nutrient Cycling in Agroecosystems, 2021)

Correction to: Consequences of the physical nature of the parent material for pedogenesis, nutrient availability, and succession in temperate rainforests - Benjamin L. Turner; Andrew Wells; Kelly M. Andersen; Leo M. Condron (Plant and Soil, 2018)

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Consequences of the physical nature of the parent material for pedogenesis, nutrient availability, and succession in temperate rainforests - Benjamin L. Turner; Andrew Wells; Kelly M. Andersen; Leo M. Condron (Plant and Soil, 2018)

Plant phosphorus availability index in rehabilitated bauxite-processing residue sand - J. B. Goloran; C. R. Chen; I. R. Phillips; Z. H. Xu; L. M. Condron (Plant and Soil, 2014)

Pedogenesis, nutrient dynamics, and ecosystem development: the legacy of T.W. Walker and J.K. Syers - Benjamin L. Turner; Leo M. Condron (Plant and Soil, 2013)

Progressive and retrogressive ecosystem development coincide with soil bacterial community change in a dune system under lowland temperate rainforest in New Zealand - Kamlesh Jangid; William B. Whitman; Leo M. Condron; Benjamin L. Turner; Mark A. Williams (Plant and Soil, 2013)

Soil microbial biomass and the fate of phosphorus during long-term ecosystem development - Benjamin L. Turner; Hans Lambers; Leo M. Condron; Michael D. Cramer; Jonathan R. Leake; Alan E. Richardson; Sally E. Smith (Plant and Soil, 2013)

Impacts of greenwaste biochar on ammonia volatilisation from bauxite processing residue sand - C. R. Chen; I. R. Phillips; L. M. Condron; J. Goloran; Z. H. Xu; K. Y. Chan (Plant and Soil, 2013)

Soil bacterial community succession during long‐term ecosystem development - Kamlesh Jangid; William B. Whitman; Leo M. Condron; Benjamin L. Turner; Mark A. Williams (Molecular Ecology, 2013)
The physicochemical and biological gradients of soil and vegetative succession along the F ranz J osef chronosequence in N ew Z ealand were used to test whether bacterial communities show patterns of change associated with long‐term ecosystem development. Pyrosequencing was conducted on soil‐derived 16S rRNA genes at nine stages of ecosystem progression and retrogression, ranging in age from 60 to c . 120 000 years since glacial retreat. B ray– C urtis ordination indicated that the bacterial communities showed clear patterns of change that were closely aligned with ecosystem development, pedogenesis and vegetative succession ( M antel test; r = 0.58; P c . 1000 years of development, when bacterial richness ( S impson's 1/ D ) declined from 130 to 30. The relatively high turnover of soil bacterial communities corresponded with an integrative ‘plant–microbial successional feedback’ model that predicts primarily negative feedbacks between plants and soil bacterial communities during progression and early pedogenesis. Positive feedbacks, similar to those of the plant community, could explain the long periods of community stability during later retrogressive stages of ecosystem development. This hypothesized model provides a consistent description linking belowground communities to ecosystem development and succession. The research, using deep sequencing technology, provides the first evidence for soil bacterial community change associated with the process of long‐term ecosystem development. How these bacterial community changes are linked to the processes of primary ecosystem succession is not known and needs further investigation.

Nanoprobing of the Effect of Cu2+ Cations on Misfolding, Interaction and Aggregation of Amyloid β Peptide - Zhengjian Lv; Margaret M. Condron; David B. Teplow; Yuri L. Lyubchenko (Journal of Neuroimmune Pharmacology, 2013)

Patterns of tree community composition along a coastal dune chronosequence in lowland temperate rain forest in New Zealand - Benjamin L. Turner; Andrew Wells; Kelly M. Andersen; Leo M. Condron (Plant Ecology, 2012)

Hippuric acid and benzoic acid inhibition of urine derived N 2 O emissions from soil - JANET E. BERTRAM; TIM J. CLOUGH; ROBERT R. SHERLOCK; LEO M. CONDRON; MAUREEN O'CALLAGHAN; NAOMI S. WELLS; JESSICA L. RAY (Global Change Biology, 2009)
Atmospheric concentrations of the greenhouse gas nitrous oxide (N 2 O) have continued to rise since the advent of the industrial era, largely because of the increase in agricultural land use. The urine deposited by grazing ruminant animals is a major global source of agricultural N 2 O. With the first commitment period for reducing greenhouse gas emissions under the Kyoto Protocol now underway, mitigation options for ruminant urine N 2 O emissions are urgently needed. Recent studies showed that increasing the urinary concentration of the minor urine constituent hippuric acid resulted in reduced emissions of N 2 O from a sandy soil treated with synthetic bovine urine, due to a reduction in denitrification. A similar effect was seen when benzoic acid, a product of hippuric acid hydrolysis, was used. This current laboratory experiment aimed to investigate these effects using real cow urine for the first time. Increased concentrations of hippuric acid or benzoic acid in the urine led to reduction of N 2 O emissions by 65% (from 17% to 2 O fluxes. This study indicates the potential for developing a novel mitigation strategy based on manipulation of urine composition through ruminant diet.

An examination of potential extraction methods to assess plant-available organic phosphorus in soil - R. W. McDowell; L. M. Condron; I. Stewart (Biology and Fertility of Soils, 2008)

Soil Organic Phosphorus Transformations During Pedogenesis - Benjamin L. Turner; Leo M. Condron; Sarah J. Richardson; Duane A. Peltzer; Victoria J. Allison (Ecosystems, 2007)

Influence of aggregate size on phosphorus changes in a soil cultivated intermittently: analysis by 31P nuclear magnetic resonance - R. W. McDowell; J. T. Scott; I. Stewart; L. M. Condron (Biology and Fertility of Soils, 2007)

Chemical Nature and Diversity of Phosphorus in New Zealand Pasture Soils Using 31P Nuclear Magnetic Resonance Spectroscopy and Sequential Fractionation - R. W. McDowell; L. M. Condron; I. Stewart; V. Cave (Nutrient Cycling in Agroecosystems, 2005)

Effects of plant species on microbial biomass phosphorus and phosphatase activity in a range of grassland soils - C. R. Chen; L. M. Condron; M. R. Davis; R. R. Sherlock (Biology and Fertility of Soils, 2004)

Effects of plant species on phosphorus availability in a range of grassland soils - C. R. Chen; L. M. Condron; S. Sinaj; M. R. Davis; R. R. Sherlock; E. Frossard (Plant and Soil, 2003)

Soil organic matter biochemistry and potential susceptibility to climatic change across the forest‐tundra ecotone in the Fennoscandian mountains - SOFIE SJÖGERSTEN; BENJAMIN L. TURNER; NATHALIE MAHIEU; LEO M. CONDRON; PHILIP A. WOOKEY (Global Change Biology, 2003)
We studied soil organic carbon (C) chemistry at the mountain birch forest‐tundra ecotone in three regions of the Fennoscandian mountain range with comparable vegetation cover but contrasting degrees of continentality and latitude. The aim of the study was to identify functional compound classes and their relationships to decomposition and spatial variation across the ecotone and latitudinal gradient. Solid‐state 13 C nuclear magnetic resonance (CPMAS 13 C NMR) was used to identify seven functional groups of soil organic C: alkyls , N‐alkyls , O‐alkyls , acetals , aromatics , phenolics and carboxyls . N‐alkyls , O‐alkyls and acetals are generally considered labile substrates for a large number of saprotrophic fungi and bacteria, whilst phenolics and aromatics are mainly decomposed by lignolytic organisms and contribute to the formation of soil organic matter together with aliphatic alkyls and carboxyls . All soils contained a similar proportional distribution of functional groups, although relatively high amounts of N‐alkyls , O‐alkyls and acetals were present in comparison to earlier published studies, suggesting that large amounts of soil C were potentially vulnerable to microbial degradation. Soil organic matter composition was different at the most southerly site (Dovrefjell, Norway), compared with the two more northerly sites (Abisko, Sweden, and Joatka, Norway), with higher concentrations of aromatics and phenolics , as well as pronounced differences in alkyl concentrations between forest and tundra soils. Clear differences between mountain birch forest and tundra heath soil was noted, with generally higher concentrations of labile carbon present in tundra soils. We conclude that, although mesic soils around the forest‐tundra ecotone in Fennoscandia are a potential source of C to the atmosphere in a changing environment, the response is likely to vary between comparable ecosystems in relation to latitude and continentality as well as soil properties especially soil nitrogen content and pH.

Effects of afforestation on phosphorus dynamics and biological properties in a New Zealand grassland soil - C. R. Chen; L. M. Condron; M. R. Davis; R. R. Sherlock (Plant and Soil, 2000)

Isotope techniques to study phosphorus cycling in agricultural and forest soils: a review - H. J. Di; L. M. Condron; E. Frossard (Biology and Fertility of Soils, 1997)